“Primary Omental Hydatid Cyst”: A Rare Entity - Shailesh Sable; Jyoti Mehta; Sudeep Yadav; Priyadarshan Jategaokar; Premashish J. Haldar (Case Reports in Surgery)
Hydatid cyst is caused by the parasite Echinococcus granulosus commonly seen in temperate regions. Primary omental hydatid cyst is rare entity. Diagnosis can be achieved with contrast-enhanced computed tomography of abdomen and pelvis along with serology. Eosinophilia is a strong pointer to hydatid cyst as a differential diagnosis. Open or laparoscopic excision of the cyst along with medical therapy remains the treatment of choice.